Update in Neurocritical Care: a summary of the 2018 Paris international conference of the French Society of Intensive Care - Oddo, Mauro (Ann Intensive Care, 2019)
The 2018 Paris Intensive Care symposium entitled “Update in Neurocritical Care” was organized in Paris, June 21–22, 2018, under the auspices of the French Intensive Care Society. This 2-day post-graduate educational symposium comprised several chapters, aiming first to provide all-board intensivists with current standards for the clinical assessment of altered consciousness states (including coma and delirium) and peripheral nervous system in critically ill patients, monitoring of brain function (specifically, electro-encephalography) and best practices for sedation—analgesia—delirium management. An update on the treatment of specific severe brain pathologies—including ischaemic/haemorrhagic stroke, cerebral venous thrombosis, hypoxic-ischaemic brain injury, immune-mediated and infectious encephalitis and refractory status epilepticus—was also provided. Finally, we discuss how to approach some difficult decisions, namely the role of decompressive craniectomy and prognostication models in patients with head injury. For each chapter, the scope of the present review was to provide important issues and key messages, provide most recent and relevant literature in the field, and briefly describe new developments in the field.